2016
DOI: 10.1007/s10529-016-2261-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of flavonoids against NS2B-NS3 protease of ZIKA virus and their structure activity relationship

Abstract: The chemical structure of a polyphenol compound and its inhibitory activity against ZIKV NS2B-NS3 can be explored to develop highly selective inhibitors against ZIKV NS2B-NS3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 19 publications
(22 reference statements)
6
56
1
2
Order By: Relevance
“…Further, the mode of inhibition was determined to be uncompetitive with inhibition constant (K i ) in low micromolar range (K i = 0.387 ± 0.034 µM). A study of polyphenols inhibiting ZIKV protease has shown that EGCG inhibits protease with higher IC50 (87 µM) values (37). Taken together, our findings suggest that EGCG may target ZIKV helicase more specifically in addition to envelope protein and NS3 protease.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Further, the mode of inhibition was determined to be uncompetitive with inhibition constant (K i ) in low micromolar range (K i = 0.387 ± 0.034 µM). A study of polyphenols inhibiting ZIKV protease has shown that EGCG inhibits protease with higher IC50 (87 µM) values (37). Taken together, our findings suggest that EGCG may target ZIKV helicase more specifically in addition to envelope protein and NS3 protease.…”
Section: Discussionmentioning
confidence: 53%
“…Also, EGCG can form the significant binding interactions at RNA site revealed by computational tools. Interestingly, the comparison with previous studies illustrate that EGCG can target multiple viral protein such as envelope (16), protease (37) and now more precisely helicase. Since EGCG has shown virucidal effect against several viruses, therefore EGCG backbone could be used to develop a broad-spectrum antiviral molecule in near future.…”
Section: Discussionmentioning
confidence: 80%
“…In this way, many natural products have been tested against NS2B-NS3 protease, and some of them were able to inhibit ZIKV protease activity. In one study, 22 compounds were tested at (the relatively high concentration of) 100 mM, and seven compounds were able to inhibit >50% of the protease activity [57]. The IC 50 s of these compounds were determined and ranged from 22 to 112 mM [57].…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
“…In one study, 22 compounds were tested at (the relatively high concentration of) 100 mM, and seven compounds were able to inhibit >50% of the protease activity [57]. The IC 50 s of these compounds were determined and ranged from 22 to 112 mM [57]. In another study, five flavonoids and one natural phenol were tested [58].…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
“…Bir başka çalışma-da, sofosbuvirin multiple insan tümör hücrelerinde ve insan nöronal sistem hücre dizilerinde Zika virus enfeksiyonlarını ve viral replikasyonu inhibe ettiği gösterilmiştir (48) . Yakın zamanda, adenozin trifosfat analoglarının Zika virusun RNA bağımlı RNA polimerazını etkili bir şekilde inhibe ettiğini ve flavonoidlerin Zika virus NS2B-NS3 proteazı üzerine inhibitör etkisi olduğunu gösteren çalışma-lar da yayımlanmıştır (49,50) .…”
Section: Tedaviunclassified